CARA BELAJAR WARGA BELAJAR PAKET B DI SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Junita, Nidia; Bahar, Aswandi; Widiastuty, Widiastuty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Programs of Sanggar Kegiatan Belajar (SKB) aim to completethe quality of education and to help people who drop out of schooltobe able tocontinue their education. The problems thatarise at Sanggar Kegiatan Belajar is the existence of some people learn not prepared to learn, people who do not follow the lessons learned seriously, the learners who do not prepareex am. The purpose of current study is to examine residents learning how to learnat Sanggar Kegiatan Belajar package B( SKB) of Pekanbaru. The population of this study is 43 student and the samples is 30 student of Sanggar Kegiatan Belajar (SKB) Pekanbaru. Research data collection was conducted by using a question naire-shaped instrument containing the statement about learning how people learn at Sanggar Kegiatan Belajar package B (SKB) Pekanbaru , amounting to 59 items. The results of data analys is showed that: 1) how to learning the way of learning to prepare in SKB Kota Pekanbaru quite good at73.7%, 2) the regularity of learning how to learn in the classroom is quite good, at 68.3%, 3) how to learning how to read book is quite good, at 62.8% . 4) in the way of learning how to write the summary is fair, at 73.8%. 5) how the lessons learned in the following manner is in excellent, at 89.6%. 6) how to memorize the lessons learned in the relatively lesswell, by 40.6%. 7) how to learn the way to take the examis in excellent, at 87.5%.Key words: How to Learn, LearningCitizen, PackageB